2013
DOI: 10.1128/aem.01087-13
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Optically Targeted Single Bacteria by Application of Fluidic Force Microscopy to Aerobic Anoxygenic Phototrophs from the Phyllosphere

Abstract: In their natural environment, bacteria often behave differently than they do under laboratory conditions. To gain insight into the physiology of bacteria in situ, dedicated approaches are required to monitor their adaptations and specific behaviors under environmental conditions. Optical microscopy is crucial for the observation of fundamental characteristics of bacteria, such as cell shape, size, and marker gene expression. Here, fluidic force microscopy (FluidFM) was exploited to isolate optically selected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 75 publications
2
35
0
Order By: Relevance
“…One such trait, as is apparent from the ubiquity of light-sensing and light protection genes, is the exposure to solar radiation. The ability to sense and utilize light by phyllosphere microbes is emerging as a general trend (39)(40)(41). Indeed, the prevalence of light-sensing and light utilization mechanisms, such as rhodopsin, PYP, and, notably, anoxygenic photosystem genes, reiterates the contention that light is an important resource and signal in the leaf surface habitat.…”
Section: Discussionmentioning
confidence: 99%
“…One such trait, as is apparent from the ubiquity of light-sensing and light protection genes, is the exposure to solar radiation. The ability to sense and utilize light by phyllosphere microbes is emerging as a general trend (39)(40)(41). Indeed, the prevalence of light-sensing and light utilization mechanisms, such as rhodopsin, PYP, and, notably, anoxygenic photosystem genes, reiterates the contention that light is an important resource and signal in the leaf surface habitat.…”
Section: Discussionmentioning
confidence: 99%
“…These observations have prompted many in the microbial ecology community to disregard community analyses that examine only those community members that are culturable. Unfortunately, only a few other studies have addressed the culturability of phyllosphere bacteria (22,23,39). The low incidence of culturability is particularly noteworthy in soil, where the apparent presence of a heterogeneous mixture of microenvironments with distinct chemical and physical restrictions presumably select for bacteria with distinct features capable of exploiting only localized regions of the soil (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study supports the findings of a few recent studies that reveal that not all habitats harbor bacteria that are similarly difficult to culture, since cultured representatives of 34 out of 40 relatively abundant (Ͼ0.2%) OTU on leaves could be recovered. Although this was surprising, it was not unprecedented; a recent study of phyllosphere bacteria using fluidic force microscopy demonstrated that 69 of 100 randomly chosen cells of clover epiphytes recovered from leaves were capable of growth in a lownutrient medium (22), and high-throughput sequencing efforts in Arabidopsis similarly found nearly 50% of the relatively abundant (Ͼ0.1%) OTU determined by direct DNA sequencing to also be represented in a library of cultured strains from these same samples (23). Furthermore, a previous study on the apple phyllosphere sequenced 300 clones and found that 85% of them corresponded to known cultured OTUs, even though 4=,6-diamidino-2-phenylindole (DAPI) staining would have indicated that less than 1% of the cells were enumerated by culturing (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides oxidation of organic carbon, utilization of sunlight may act as accessory mode of energy conservation for phyllosphere bacteria (53,54). The M. extorquens PA1 genome encodes for proteins of aerobic anoxygenic photosynthesis and photosynthetic cytochrome PufC (Mext_2738) was among the most up-regulated proteins in planta (Table I).…”
Section: Swath Assaymentioning
confidence: 99%